MENGIMPLEMENTASIKAN PEMBENTUKAN KARAKTER SISWA DI SEKOLAH DASAR MELALUI KEBUDAYAAN DAERAH KLATEN - Erni Setyowati; Akbar Al Masjid (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to implement the formation of student character through the local culture of Klaten with a focus on the character of cooperation, the character of mutual cooperation, and the character of students' harmonious life. This research uses a literature study method thatanalyzes or observes various data and sources related to the implementation of the Klaten regional culture into learning in elementary schools, especially in the formation of student character. Literature sources can be in the formof articles, books, reports, information from the public, and others. The results of the study show that the implementation of the Klaten regional culture in learning in elementary schools can be done by presenting learning carried out by the teacher, namely the teacher gives group assignments so that these students apply the character of cooperation, mutual cooperation and live in harmony at school. This learning can be done contextually, namely where learning is based on real conditions or occurs in the environment around students which aims to make student learning meaningful. The implementation of the Klaten regional culture in elementary schools can instill educational values, norms, and attitudes instudents.